2017
DOI: 10.5552/drind.2017.1701
|View full text |Cite
|
Sign up to set email alerts
|

Impregnability of Paulownia and Populus Wood with Copper Based Preservatives

Abstract: • The importance of fast growing wood species such as Paulownia and Populus wood is increas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…6]. These results could be explained by the chromatographic effect, which is observed in situations where the solvent penetrates faster than the dissolved active ingredient similar to chromatography (Rasouli et al 2017). Other influencing factors could be Cu compound chemical and physical fixation in the wood structure, which restricts further penetration (Temiz et al 2014).…”
Section: Impregnation Efficiency Of Glued Wood Specimensmentioning
confidence: 99%
“…6]. These results could be explained by the chromatographic effect, which is observed in situations where the solvent penetrates faster than the dissolved active ingredient similar to chromatography (Rasouli et al 2017). Other influencing factors could be Cu compound chemical and physical fixation in the wood structure, which restricts further penetration (Temiz et al 2014).…”
Section: Impregnation Efficiency Of Glued Wood Specimensmentioning
confidence: 99%
“…There has been much research on wood treated with micronized systems over the past 10 years. Since these preservatives are introduced to the wood as particles rather than in a soluble solution there is concern that they do not penetrate the wood cell wall as well, especially in refractory species [ 11 , 12 ]. In a recent review, Tarmian [ 13 ] concluded that “micronized copper-based preservatives cannot penetrate as deeply or uniformly as the soluble copper-based ones”.…”
Section: Introductionmentioning
confidence: 99%